2023
DOI: 10.1007/s12021-023-09646-2
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning-Based Ensemble Method for Early Diagnosis of Alzheimer’s Disease using MRI Images

Sina Fathi,
Ali Ahmadi,
Afsaneh Dehnad
et al.

Abstract: Recently, the early diagnosis of Alzheimer’s disease has gained major attention due to the growing prevalence of the disease and the resulting costs imposed on individuals and society. The main objective of this study was to propose an ensemble method based on deep learning for the early diagnosis of AD using MRI images. The methodology of this study consisted of collecting the dataset, preprocessing, creating the individual and ensemble models, evaluating the models based on ADNI data, and validating the trai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Once, Arafa et al 17 used a traditional CNN model for the classification of mild-dementia and non-dementia with an accuracy of 99.99%. And Fathi et al 18 applied six CNN classifiers to form an integrated model with up to 93.92% accuracy. Then, Helaly et al 19 used the traditional CNN model, the classification accuracies for 2D and 3D data of AD were 93.61 and 95.17%, respectively, and VGG19 models for transfer learning with up to 97% accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Once, Arafa et al 17 used a traditional CNN model for the classification of mild-dementia and non-dementia with an accuracy of 99.99%. And Fathi et al 18 applied six CNN classifiers to form an integrated model with up to 93.92% accuracy. Then, Helaly et al 19 used the traditional CNN model, the classification accuracies for 2D and 3D data of AD were 93.61 and 95.17%, respectively, and VGG19 models for transfer learning with up to 97% accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Fathi et al. ( 30 ) introduced a weighted probability-based ensemble method to combine six 2D-CNN architectures and obtain a high classification rate of 93.88 for four classes. Furthermore, they compared different ensemble methods and showed that the ensemble methods yielded better results than individual architectures.…”
Section: Introductionmentioning
confidence: 99%